A decision-making LCA for energy refurbishment of buildings: Conditions of comfort - Assiego-de-Larriva, Rafael; Calleja Rodríguez, Gloria; Cejudo-López, José Manuel; Raugei, Marco; Fullana i Palmer, Pere (Elsevier, 2014)
This paper is focused on providing information to help in decision-making between five different scenarios for energy refurbishment, evaluating the lifecycle of each and also taking into consideration the level of comfort in dwellings. This work centres on one block built in 1983 in which temperatures have been monitored which show that the optimum temperature conditions are not reached for long periods during the year. The current state of the building is referred to as scenario one. Energy consumption is evaluated considering the lifecycle of the components necessary for the refurbishment, their subsequent operation and disposal. All scenarios address the suitability of passive measures or the implementation of active systems in temperate climates under the assumption that comfort in dwellings is achieved. Scenarios two and three are assessed applying insulation and changing the windows. The fourth and fifth implement an alternative solution, a controlled mechanical ventilation based on a typical mild climate cross ventilation. Evaluation uses two environmental indicators, gross energy requirement (GER) and global warming potential (GWP). It is concluded that scenarios four and five reduce the GER in 4.4 and 9%, respectively, and the GWP in 2.6 and 4.3% compared to the current state.
Keywords: Viviendas - Consumo de energía; Life cycle assessment (LCA); Energy refurbishment; Thermal confort; Functional unit; Communication of results